037 Post-transplant lymphoproliferative disorder in skeletal muscle arising seven years after allogeneic stem cell transplant. Issue 6 (24th May 2018) - Powell, Alice; Sy, Joanne; Barnett, Yael; Mosalski, Simon; Brew, Bruce; Fay, Keith; Tomlinson, Susan
Abstract : Introduction: Post-transplant lymphoproliferative disorder (PTLD) is a well-recognised serious complication of transplantation. However, it rarely affects muscle. Methods: A case report detailing presentation, evaluation, management and outcome of a patient with acute on chronic proximal myopathy on a background of allogeneic stem cell transplant is described. The patient was diagnosed with PTLD affecting skeletal muscle. Results: A 54 year old man presented with painful proximal myopathy seven years after successful allogeneic stem cell transplant for acute myeloid leukaemia. He had been managed with immunosuppression for extensive cutaneous graft versus host disease (GVHD) from the time of transplant. Initial quadriceps muscle biopsy showed changes in keeping with GVHD and features suggestive of drug-related necrotising myositis. The painful myalgia evolved to include bulbar muscles with dysphagia despite pulse steroid and intravenous immunoglobulin therapy. A positron emission tomography (PET) scan demonstrated intense and extensive hyper-metabolism in multiple muscle groups in keeping with diffuse myositis with the most prominent activity involving neck muscles, the left shoulder girdle and left arm musculature. A second biopsy of the sternocleidomastoid demonstrated infiltration with haematolymphoid cells consistent with post-transplant lymphoproliferative disorder. Treatment with reduction in immunosuppression, rituximab and rehabilitation saw improvement in myalgia and weakness. Unfortunately, exacerbation of chronic GVHD ensued following reduction in immunosuppression and contributed to oesophageal stricturing eventually requiring a percutaneous endoscopic gastrostomy tube for feeding. Conclusion: This case highlights the complex morbidity of allogeneic stem cell transplant and the need to consider PTLD in the differential for patients who present with neurological symptoms.